When is age dissimilarity harmful for organisational identification? The moderating role of age stereotypes and perceived age-related treatment. (June 2021) - Sammarra, Alessia; Profili, Silvia; Peccei, Riccardo; Innocenti, Laura
Due to demographic changes, age diversity is growing in the workplace, creating a potential challenge to social integration. However, who is most affected by working with colleagues of different ages and when is being dissimilar in age from others more likely to hinder organisational identification? Drawing on relational demography and on the social identity approach, we suggest that certain individual and contextual conditions can lead employees to react to greater age dissimilarity by reducing their psychological attachment to the organisation. We propose that negative age stereotypes and perceived age-related treatment affect the salience of age as a social category for employees and threaten their age group identity, thereby creating conditions in which age dissimilarity might hinder organisational identification. We therefore examine the moderating effects of negative age stereotypes and perceived age-related treatment on the relationship between age dissimilarity and organisational identification in a sample of 434 schoolteachers from 16 schools in Italy. Findings show that age dissimilarity per se is not sufficient to hamper employees' identification with the organisation. However, it has detrimental effects when employees hold negative age stereotypes and/or perceive an unfair organisational treatment towards their own age group. Implications for research are discussed along with practice implications.